Melastoma malabraticum L as Potential Inducer in Spawning Process and Number of Daphnia sp. Offspring. Issue 1 (1st September 2022) - Farizah, Nuril; Zairin, Muhammad; Darusman, Latifah K; Boediono, Arief; Suprayudi, Muhammad Agus
Abstract: The aimed of the study was to evaluate the ethanol extract of M. malabraticum L as an inducer in the spawning process and the number of juvenile daphnids from Parthenogenesis femaleof Daphnia sp. The experiment was divided into two stages. Firstly, the experiment consisted of the phytochemical screening of medicinal plants, M. malabraticum L isolation and characterization of the bioactive compound through GC-MS. Secondly, the extraction of M. malabraticum L leaf, the production of Parthenogenesis female and in vivo assay on daphnia sp. The experiment composed of four treatment groups with four replicates. The concentration of immersion varied from 50, 100, 200 ppm of the examined ethanol extract of M. malabraticum L and control. The results showed that the treatment of Melastoma extracts significantly affected (P <0, 05) on spawning rate on Parthenogenesis femaleof Daphnia sp compared to control treatment while for the number of offspring produced was significantly different (P <0, 05). The treatment of immersion extract with concentration 50 ppm showed the highest number of offspring (53.67 ± 2.52), while the other treatment was the concentration of 100 ppm (51.00 ± 1.00), the concentration of 200 ppm (33.33 ± 3.06) and control treatment (44.33 ± 1.53). Administration of ethanol extract Melastoma malabraticum L with different concentrations, by immersion significantly affected to spawning rate and the number of Daphnia sp offspring. The melastoma extract treatment with the concentration of 50 ppm showed 100% spatial, spread rate and the highest number of offspring.